2006
DOI: 10.1016/j.jhydrol.2006.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal rainfall variability in mountainous areas: A case study from the south Ecuadorian Andes

Abstract: Particularly in mountain environments, rainfall can be extremely variable in space and time. For many hydrological applications such as modelling, extrapolation of point rainfall measurements is necessary. Decisions about the techniques used for extrapolation, as well as the adequacy of the conclusions drawn from the final results, depend heavily on the magnitude and the nature of the uncertainty involved. In this paper, we examine rainfall data from 14 rain gauges in the western mountain range of the Ecuadori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
228
1
26

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 377 publications
(274 citation statements)
references
References 12 publications
(14 reference statements)
10
228
1
26
Order By: Relevance
“…[34] The absence of a dry season [Buytaert et al, 2006b], and the marked drop of soil hydraulic conductivity in nonsaturated conditions result in continuously wet soils (>60 vol% [Buytaert et al, 2005]). Field research has shown that also in dry periods a saturated soil layer exists above the bedrock, even on steep slopes [Buytaert et al, 2005].…”
Section: Hydrological Modelmentioning
confidence: 99%
“…[34] The absence of a dry season [Buytaert et al, 2006b], and the marked drop of soil hydraulic conductivity in nonsaturated conditions result in continuously wet soils (>60 vol% [Buytaert et al, 2005]). Field research has shown that also in dry periods a saturated soil layer exists above the bedrock, even on steep slopes [Buytaert et al, 2005].…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Nevertheless the need to consider comprehensive data set is important in the Andean regions. Rainfall tends to decrease with altitude, but the windward or leeward exposure of the stations to the dominant moist wind makes it difficult to find a simple relationship between rainfall and altitude (Johnson, 1976;Roche et al, 1990;Guyot, 1993;Pulwarty et al, 1998;Buytaert et al, 2006;Ronchail and Gallaire, 2006;Laraque et al, 2007). On the contrary, in Brazil, the spatiotemporal rainfall variability has been more widely studied and published than in the Andean countries.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing precipitation is expected to occur with increasing elevation (Spreen, 1947;Arora et al, 2006). Since steeper slopes provide stronger orographic lifting, increasing slope or standard deviation is expected to be associated with higher rainfall (locally, at least; Buytaert et al, 2006). It is anticipated that the spatial scale at which these processes occur will vary month to month due to different synoptic forcings, wind patterns, and other seasonal variations (e.g.…”
Section: Hypothesesmentioning
confidence: 99%